Systemic Corticosteroids are Effective in about a Half of pemphigus Patients - Anfisa Lepekhova (Journal of Global Pharma Technology, 2020)
Systemic corticosteroids (CS) can control flare-ups of the disease and remain the mainstay of treatment. However, even high doses of CS sometimes fail to produce adequate symptom control. We retrospectively analyzed the rate of CS efficacy in 123 pemphigus patients seen at our Department over 16-year period. Our research shows that half (54/123) of patients with pemphigus had lack of response to treatment. PNP was noted only in CS resistant patients (8/54). Also, higher mortality, at least one exacerbation a year and exacerbation during 2-5 year of the disease associated with reduction of CS dose were significantly more frequent in the group of CS resistant patients than in CS sensitive one.We showed that half of patients had a lack of response to CS. However, we found in pemphigus onlyclinical severity subdivision by frequency and clinical manifestations of steroid resistance useful in adjuvant therapy. Adjuvant therapy can beused to treatpemphigus vulgaris to reduce sideeffects of CS or when these therapies are ineffective to achieve a complete remission.Therefore, it is important to investigate a potential molecular biomarkers of CS resistance in patients with pemphigus and other bullous disorders. Keywords: Pemphigus, Steroid insensitivity, Potential biomarkers, Criteria of steroid insensitivity, Severity, Treatment.